2018
DOI: 10.1159/000490659
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma Arising from Perianal Fistulizing Crohn’s Disease

Abstract: Perianal fistula is a very debilitating event and a cause of morbidity in patients with Crohn’s disease (CD). Its malignant transformation is very rare with an incidence of around 0.004–0.7%. Presence of disease in the colon and rectum is the major risk factor for the development of a perianal fistula. In this report we show a case of adenocarcinoma arising from a perianal fistulizing CD. This type of tumor is highly aggressive, difficult to diagnose, and has a rather poor prognosis. The different neoplastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…25 Despite the identification of these characteristics seen on MRI, it appears that these findings are often not so helpful in practice. 15,21 Additionally, some studies report the use of fluorodeoxyglucose positron emission tomography (PET) with inability to differentiate between benign inflammation and malignancy.…”
Section: Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…25 Despite the identification of these characteristics seen on MRI, it appears that these findings are often not so helpful in practice. 15,21 Additionally, some studies report the use of fluorodeoxyglucose positron emission tomography (PET) with inability to differentiate between benign inflammation and malignancy.…”
Section: Presentation and Diagnosismentioning
confidence: 99%
“…6,12,14 Additionally, fistulas that are at higher risk of harboring malignancy are typically chronic and longstanding in nature, with an average duration of 10 years. 15 This suggests that early and definitive management of perianal fistulous disease may lead to significant reduction in risk of developing FAAC. 16 As always, there are exceptions to this rule.…”
Section: Risk Factorsmentioning
confidence: 99%
“…93 The possible role of exosomes in the progression of the perianal fistula has not yet been demonstrated, but there are reports on their role in other alimentary tract diseases. Because the perianal fistula is pathologically related to excessive inflammation, 89,94 there might be a relationship be-tween perianal fistula and exosome function. Accordingly, Topal et al showed that the intestinal lumen is an excellent source of exosomes carrying different kinds of mRNAs and proteins to regulate mucosal cells.…”
Section: Exosome Therapymentioning
confidence: 99%